Kondisi Keuangan, Kualitas Pelayanan, Sanksi Perpajakan, Kesadaran dan Kepatuhan Wajib Pajak Kendaraan Bermotor - Surya Dharma, Ida Bagus Alit; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2021)
This study aims to obtain empirical evidence of the influence of the taxpayer's financial conditions, service quality, taxation sanctions, and taxpayer awareness on motor vehicle taxpayer compliance. This study uses primary data. Samples were taken using accidental sampling method and this research was conducted at the Bali Provincial Revenue Agency in 2017. The number of respondents was 100 taxpayers. Data was collected using questionnaires and analyzed using multiple linear regression. Based on the results of the analysis, the results obtained that the financial condition of the taxpayer, service quality, taxation sanctions, and taxpayer awareness have a positive effect on motor vehicle taxpayer compliance at the Bali Provincial Revenue Agency. Keywords: Taxpayer's Financial Condition, Service Quality; Taxation Sanction; Taxpayer Awareness; Mandatory Vehicle Compliance.